Synthesis and characterization of cu-doped ZnO nanorods - Pung, S.Y.; Ong, C.S.; Mohd Isha, K.; Othman, M.H. (Universiti Kebangsaan Malaysia, 2014)
Cu-doped ZnO nanorods were synthesized by sol-gel method using zinc nitrate tetrahydrate, methenamine and cupric acetate monohydrate as precursors. The as-synthesized ZnO nanorods have a twin-rod structure. The polar (002) surface of ZnO nanorods, which could be either negatively charge (O-terminated) or positively charged (Zn-terminated), was responsible for the formation of twin-rod structure. The results showed that the size, aspect ratio, crystallinity and c-lattice parameter of Cu doped ZnO nanorods decreased with increasing of Cu dopant concentration. In fact, the presence of Cu retarded the growth of ZnO nanorods in its preferred growth direction, i.e. (0001). The XPS analysis indicates that Cu ions were oxidized (Cu2+) and substituted into the ZnO lattice at the Zn2+ site. The presence of Cu reduced the optical bandgap of ZnO from 3.34 eV (undoped ZnO nanorods) to 3.31 eV (20 mol% Cu doped ZnO). Besides, it induced a visible PL emission at 2.97 eV, which could be related to the transition of electrons from conduction band (Ec) to Cu acceptor energy level (Ev + 0.45 eV) radiatively.